Entry cost based on activity-based cost specifications and comparative study - سرور, منال جبار; عبد الرضا, ضرغام احمد (Journal of Economics and Administrative Sciences, 2016)
Several recent approaches focused on the developing of traditional systems to measure the costs to meet the new environmental requirements, including Attributes Based Costing (ABCII). It is method of accounting is based on measuring the costs according to the Attributes that the product is designed on this basis and according to achievement levels of all the Attribute of the product attributes. This research provides the knowledge foundations of this approach and its role in the market-oriented compared to the Activity based costing as shown in steps to be followed to apply for this Approach. The research problem in the attempt to reach the most accurate Approach in the measurement of the cost of products from the Approaches (ABC) and (ABCII), and research aims mainly to indicate the role of the Attribute Based Costing Approach to provide the most accurate cost information compared to the Activity Based Costing Approach It works to meet the needs and desires of customers as the application starts by identifying customer specifications and characteristics desired by the customer in the product.